Asset growth, operational efficiency, and firm value : The mediating role of profitability in Indonesian banking - Samrotus Sa’adah Putri Auliatul Jannah; Mardiyani Mardiyani; Agustina Agustina (Universitas Nusa Cendana, 2026)
This study examines the influence of asset growth and operational efficiency on firm value, with profitability serving as a mediating variable among banking firms listed on the Indonesia Stock Exchange during the 2022–2024 period. In an increasingly competitive banking environment, improving financial performance has become essential for enhancing firm value and maintaining investor confidence. Employing a quantitative research design, the study utilized secondary data obtained from annual financial reports of 23 banking companies selected through purposive sampling, resulting in 69 firm-year observations. Data were analyzed using path analysis with LISREL to examine both direct and indirect relationships among the variables. The findings reveal that asset growth positively influences profitability, indicating that the effective expansion of corporate assets contributes to improved financial performance. Operational efficiency was also found to significantly affect both profitability and firm value, highlighting the importance of efficient resource management in generating sustainable corporate outcomes. Furthermore, profitability exerts a positive influence on firm value and successfully mediates the relationships between asset growth and firm value, as well as between operational efficiency and firm value. These results underscore the critical role of profitability as a strategic mechanism through which growth and operational efficiency translate into enhanced firm value. The study contributes to the literature on corporate finance and banking performance by providing empirical evidence on the interconnected roles of growth, efficiency, and profitability in creating shareholder value within emerging financial markets. Keywords: Asset Growth; Operational Efficiency; Firm Value